Case report: Severe rhabdomyolysis and acute liver injury in a high-altitude mountain climber - Yeh, Yun-Chih; Chen, Chien-Chou; Lin, Shih-Hua (Frontiers in Medicine, 2022)
Concurrent severe rhabdomyolysis and acute liver damage are rarely reported in the setting of acute high-altitude illness (AHAI). We described a 53-year-old healthy mountain climber experiencing headache and dyspnea on the summit of Snow Mountain (Xueshan, 3886 meters above sea level) presented to emergency room with generalized malaise, diffuse muscle pain, and tea-colored urine. His consciousness was alert with a blood pressure 114/74 mmHg, heart rate 66/min and body temperature 36.8。C. Myalgia over bilateral lower limbs, diminished skin turgor, dry oral mucosa, and tea-colored urine were notable. Urinalysis showed positive occult blood without red blood cells. The most striking blood laboratory data included creatine kinase (CK) 33765 IU/L, inappropriately high aspartate aminotransferase (AST) 2882 IU/L and alanine aminotransferase (ALT) 2259 IU/L (CK/AST ratio 11.7, CK/ALT ratio 14.9), creatinine 1.5 mg/dL, serum urea nitrogen (BUN) 14 mg/dL, total bilirubin 1.7 mg/dL, ammonia 147 μg/mL, lactate 2.5 mmol/L and prothrombin time 17.8 seconds. The meticulous search for the underlying causes of acute liver injury was non-revealing. With volume repletion, mannitol use, and urine alkalization coupled with avoidance of nephrotoxic and hepatotoxic agents, his clinical features and laboratory abnormality are completely resolved in 3 weeks. Despite rarity, severe rhabdomyolysis and/or acute liver injury as a potential life-threatening condition requiring urgent management may occur in high-altitude hypobaric hypoxia.